Chemisorption of a Strained but Flexible Molecule: Cyclooctyne on Si(001). Issue 23 (28th February 2017) - Pecher, Josua; Schober, Christoph; Tonner, Ralf
Abstract: Invited for the cover of this issue is the group of Ralf Tonner at the University of Marburg. The image depicts the anchoring of cyclooctyne to a Si(001) surface. Read the full text of the article at 10.1002/chem.201605952 . Abstract : " The way in which cyclooctyne binds to the silicon surface makes it an ideal candidate for the construction of organic/semiconductor interfaces ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 5459 ff. (DOI:10.1002/chem.201605952 ).